Capacidade antioxidante in vitro e avaliação da toxicidade aguda in vivo de extratos de folhas de Licania rígida Benth., Licania tomentosa (Benth.) Fritsch e Couepia impressa Prance (Chrysobalanaceae) - Macedo, José Benilson Martins (2011)
Licania rigida Benth., Licania tomentosa (Benth.) Fritsch, and Couepia impressa Prance (Chrysobalanaceae family) plants have long been used medicinally by the people from Northeastern Brazil. Crude extracts and infusions of these plants have been applied in the treatment of several conditions such as diabetes and rheumatism, degenerative diseases with involvement of reactive oxygen species (ROS). The aim of this study was to evaluate the aqueous, ethanolic, and hydroethanolic leaves extracts antioxidant capacity of these species, using several in vitro assay systems (reducing power, DPPH● scavenging, the β-carotene linoleate model system and lipid peroxidation inhibition in rat brain homogenate, using thiobarbituric acid reactive substances - TBARS). The oral acute toxicity of aqueous extracts was also evaluated in vivo. Results revealed that these extracts possess a potent reducing power and DPPH scavenging ability, as well as the ability to prevent TBARS formation in rat brain homogenate in a concentration-dependent manner. Regarding in vivo oral acute toxicity of the aqueous species extracts, no toxic effects were observed upon evaluating physiological, hematological and biochemical parameters. The presence of high levels of phenolics and flavonoids was determined mainly in the ethanol extract. However, the C. impressa hydroethanolic extract, fractionated with hexane, chloroform and ethyl acetate for analysis by NMR 1H, showed more efficient results than the reference antioxidant Carduus marianus. The classes of organics compounds were determined were phenolics in the fraction of ethyl acetate and terpenes in chloroform and hexane fractions. The ethil acetate fraction had the highest content of flavonoids and increased scavenging capacity of DPPH●, possibly by the presence of phenolic compounds. Therefore, a detailed investigation of the phytochemical composition and in vivo study of the C. impressa hydroethanolic extract is suggested to characterize the active compounds of the species